Bronchiectasia and Functional Limitation in Treated Pulmonary Tuberculosis - Uribe Barreto, Alfonzo (2000)
OBJECTIVES: To establish of bronchiectasis and functional limitation frequency in patients with sequelae of pulmonary tuberculosis. MATERIAL AND METHODS: We assessed ten patients with history of pulmonary tuberculosis (one single episode) through standard radiological chest films, conventional computarized tomography (CT), bronchofibroscopy (BFC) and spirometry (SP). RESULTS: The radiological examination of the chest suguested that 50% of the patients had bronchiectasis (Gudbjerg’s criteria), confirmed CT in 90% and BFC in 100%. Forty percent of the patients had mild functional restriction, 40% moderate functional restriction and in 20% the SP was normal. CONCLUSIONS: Pulmonary tuberculosis yields bronchiectasis in almost all patients (90% TC, 100% BFC) and generates functional limitation in 80% of the cases.